Expanding Access: Opportunity to Strengthen Food Security during the Covid-19 Pandemic (A Study on the Poor in Tamansari District, Tasikmalaya City) - Nasution, Fatimah Zahra; Surgawati, Iis (Faculty of Economics and Business, Jenderal Soedirman University, 2023)
This study aims to estimate food security maps, measuring opportunities for physical access, economic access, and social access to food both partially and jointly in strengthening food security and to test the independence between food security and poverty during the Covid-19 pandemic in poor households in Tamansari District, Tasikmalaya City. The research method used is the explanatory method, while the data analysis method uses proportion estimation and regression analysis and the Chi-Square test. The results showed that during the Covid-19 pandemic, it was estimated that there were around 1.34% to 10.66% of poor people in Tamansari District, Tasikmalaya City who were classified as